2018
DOI: 10.26226/morressier.5ab4d4efd462b80296ca4d6b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Radial Extracorporeal Shock Wave Therapy on Post-Stroke Hand Spasticity

Abstract: Ѓеракароска-Савевска. Оваа статија е со отворен пристап дистрибуирана под условите на нелокализирана лиценца, која овозможува неограничена употреба, дистрибуција и репродукција на било кој медиум, доколку се цитираат оригиналниот(ите) автор(и) и изворот. Конкурентски интереси: Авторот изјавува дека нема конкурентски интереси.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…After six times of rESW treatment, the efficacy was evaluated according to the modified Ashworth scale (MAS) and disability rating scale (DAS) scores before treatment, after the sixth treatment, and 1 and 3 months after the end of treatment respectively. The results showed that ESW could improve the spasticity of wrist and finger flexors after stroke, and the effect was continuous ( 82 ). Daliri et al observed 15 patients with wrist flexor spasm after stroke one time of comfort treatment and one time of routine ESWT 1 week later, and recorded the changes of motor function at each stage in the MAS score, Hmax/Mmax value and Brunstrom evaluation method.…”
Section: Clinical Study Of Eswt In the Treatment Of Upper Limb Spasti...mentioning
confidence: 99%
“…After six times of rESW treatment, the efficacy was evaluated according to the modified Ashworth scale (MAS) and disability rating scale (DAS) scores before treatment, after the sixth treatment, and 1 and 3 months after the end of treatment respectively. The results showed that ESW could improve the spasticity of wrist and finger flexors after stroke, and the effect was continuous ( 82 ). Daliri et al observed 15 patients with wrist flexor spasm after stroke one time of comfort treatment and one time of routine ESWT 1 week later, and recorded the changes of motor function at each stage in the MAS score, Hmax/Mmax value and Brunstrom evaluation method.…”
Section: Clinical Study Of Eswt In the Treatment Of Upper Limb Spasti...mentioning
confidence: 99%